2002
DOI: 10.1001/archneur.59.8.1267
|View full text |Cite
|
Sign up to set email alerts
|

Differential Diagnosis of Alzheimer Disease With Cerebrospinal Fluid Levels of Tau Protein Phosphorylated at Threonine 231

Abstract: Increased levels of CSF p-tau(231) may be a useful, clinically applicable biological marker for the differential diagnosis of AD, particularly for distinguishing AD from FTD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
149
3
5

Year Published

2003
2003
2014
2014

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 241 publications
(165 citation statements)
references
References 27 publications
8
149
3
5
Order By: Relevance
“…Moreover, cognitive decline is correlated with CSF increasing levels of P-tau, these CSF tau species might specifically mark a cerebral degenerative process (Maccioni, Lavados et al 2006;Wallin, Blennow et al 2006). While other P-tau species have been measured, only CSF levels of tau proteins phosphorylated at serine 181 (P-tau 181 ) or threonine 231 (P-tau 231 ) seem to clearly improve the accuracy of the diagnostic of AD (Buerger, Zinkowski et al 2002;Hampel and Teipel 2004;Mitchell 2009). Some phosphorylations are more specific for AD, CSF P-tau 181 significantly increases in AD patients compared to patients without neurodegenerative processes as well as patients with other neurodegenerative dementias (Vanmechelen, Vanderstichele et al 2000;Vanderstichele, De Vreese et al 2006).…”
Section: Which Csf Biochemical Markers Might Allow Us To Detect Alzhementioning
confidence: 99%
“…Moreover, cognitive decline is correlated with CSF increasing levels of P-tau, these CSF tau species might specifically mark a cerebral degenerative process (Maccioni, Lavados et al 2006;Wallin, Blennow et al 2006). While other P-tau species have been measured, only CSF levels of tau proteins phosphorylated at serine 181 (P-tau 181 ) or threonine 231 (P-tau 231 ) seem to clearly improve the accuracy of the diagnostic of AD (Buerger, Zinkowski et al 2002;Hampel and Teipel 2004;Mitchell 2009). Some phosphorylations are more specific for AD, CSF P-tau 181 significantly increases in AD patients compared to patients without neurodegenerative processes as well as patients with other neurodegenerative dementias (Vanmechelen, Vanderstichele et al 2000;Vanderstichele, De Vreese et al 2006).…”
Section: Which Csf Biochemical Markers Might Allow Us To Detect Alzhementioning
confidence: 99%
“…61 The 20 largest studies 14,20,24,41,50,56,[62][63][64][65][66][67][68][69][70][71][72][73][74][75] including more than 2000 AD patients and 1000 controls, evaluating the most commonly used ELISA method for T-tau in CSF, 14 are summarized in Table 2. The mean sensitivity to discriminate AD from nondemented aged individuals has been 81%, at a specificity level of 91% (Table 2).…”
Section: Csf T-taumentioning
confidence: 99%
“…Normal CSF levels of P-tau are found in psychiatric disorders such as depression, 14,96 in chronic neurological disorders such as amyotrophic lateral sclerosis and PD, 14,52,70 and also in other most cases with other dementia disorders such as VAD, FTD, and LBD. 21,52,70,71,86,92,93 Furthermore, although there is a very marked increase in CSF T-tau in CJD, most patients with CJD have normal or only mildly elevated CSF P-tau. 26 In a large set of patients with CJD cases and other dementias, the ratio of P-tau to T-tau in CSF was found to discriminate CJD from other neurodegenerative disorders without any overlap.…”
Section: Csf P-taumentioning
confidence: 99%
“…The study revealed that each of the three p-tau markers is significantly elevated in AD compared with the other groups, while p-tau231 provides the greatest discrimination between AD and other neurological disorders, and the combination of all three does not augment the discrimination [61,62] . Similarly, several other studies have revealed that p-tau231 and p-tau199 can discriminate AD from other dementias with sensitivities and specificities in the range of 80-90% [63][64][65] . It is worth noting that, as a microtubule-associated protein, hyperphosphorylation of neurofilaments potentially differentiates AD from both normal aging and other dementias [66] .…”
Section: Csf T-tau and P-tau As Biomarkers Of Admentioning
confidence: 63%